The mediation bodies of the Catholic Church in Poland. The perspective of canon law - Jaworski, Karol (Prawo Kanoniczne, 2023)
This paper discusses the use of mediation in the Roman Catholic Church in Poland in the light of canon law. The first part of this article describes the theological and legal foundations of mediation and other ADR methods in the Catholic Church. The main part of this work presents the results of research on the state of development of mediation bodies in the Catholic Church in Poland. At the end, the author formulates conclusions and postulates de lege ferenda.